PENGARUH PEMBELAJARAN BERBASIS KEARIFAN LOKAL PATI BERBANTUAN MODUL PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI JRAHI 01 - Aprita Nur Damayanti; Ika Oktavianti; Sekar Dwi Ardianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACTThe learning process in this is how learning effect after using of learning based local wisdom can increase the average learning outcomes. The purpose of this research it was to increase the average learning outcomes of the four grade students of SD Negeri Jrahi 01 by using local wisdom - based learning assisted lerning modules and the effect can be known. This quantitative research was carried out at SD Negeri Jrahi 01 Pati Regency with the research subjects being 20 students with 7 male students and 13 female students. This study used the One Group Pretest Postest research design with data collection techniques used including pretest and posttest questions as well as documentation. Data analysis to be used is quantitative analysis using statistical formulas with explanatory descriptions. The form of a test is using Pired T-test and N-gain. The result of the research shows that there is increase the average learning outcames of the four grade students of SD Negeri Jrahi 01 before and after taught by using learning effects pati local wisdom - based assisted learning modules. Before using research (pretest) get the average learning outcomes 60,5 and after using research (postest) get the average 80,5 means there is an increase of 15%. It can be concluded of local wisdom based learning assisted by learning moduls can be affect learning outcomes of the four grade students of SD Negeri Jrahi 01.